Enhanced electrochemical production and facile modification of graphite oxide for cost-effective sodium ion battery anodes. (15th June 2021) - Zhang, Yubai; Qin, Jiadong; Lowe, Sean E.; Li, Wei; Zhu, Yuxuan; Al-Mamun, Mohammad; Batmunkh, Munkhbayar; Qi, Dongchen; Zhang, Shanqing; Zhong, Yu Lin
Abstract: Sodium-ion batteries (SIBs) are emerging as an inexpensive and more sustainable alternative to lithium-ion batteries in the energy storage market. To advance their commercialization, one major scientific undertaking is to develop low-cost, reliable anode materials from abundant resources, like the success of graphite in the lithium-ion batteries. However, graphite is chemically inactive in storing sodium ions and, to render it viable in sodium-ion batteries, additional modification of graphite is required. Herein, we demonstrate a green and facile method to prepare cost-effective and stable graphitic SIB anodes. The modification process started with the electrochemical oxidation of expanded graphite to widen the interlayer and functionalize graphite layers, followed by a fast (20 min) thermal treatment at 150 °C to achieve controlled deoxygenation. The thermally processed electrochemical graphite oxide could provide a high reversible capacity of 268 mAh g −1 at 100 mA g −1 and 163 mAh g −1 at 500 mA g −1 as well as low fading in capacity (in average 0.0198% loss per cycle) over 2000 cycles. The electrochemical route eliminates the need for the harsh chemical oxidation of graphite, offering a promising approach for industrial production of low-cost anodes for sodium-ion batteries. Graphical abstract: Image 1